(untitled) (Singaporean Journal of Business Economics and Management, 2018)
The study investigates the impact of the use of various long term funds on the performance of Nigerian companies. Secondary data were collected from the case study, Unilever Nig. Plc which was picked through purposive sampling method. Analysis of data was done by using multiple regression of the ordinary least square (OLS) method on the data extracted from twelve years financial statements of the company to test for the relationship between its capital mix and its value, measured in terms earnings per share (EPS). The findings show that both long term debt and profit have positive correlation with EPS, while equity is negatively correlated with EPS. The overall result was statistically significant with F-ratio value of 690. Based on the results, the financial managers of corporations are advised to always embark on appropriate financial mix between equity and debt alongside retained earnings that will maximised the returns to shareholders and monitor other market variables that may serve as constraints in achieving the overall goals of their companies.